RESPON RISIKO DAN MITIGASI RISIKO PADA FAKTOR-FAKTOR PENYEBAB WASTE KONSTRUKSI DENGAN MENGGUNAKAN PENDEKATAN LEAN CONSTRUCTION (STUDI KASUS: PROYEK X KAPUAS) - Oryza Lhara Sari; Doni Rahman Maulana (Racic : Rab Construction Research, 2023)
Waste is a problem that often occurs in construction projects. Waste is in the form of activities that utilize resources but do not produce the expected added value (value). Therefore, it is necessary to identify waste, in this research we identify the factors that cause construction waste in the rehabilitation project and improvement of irrigation networks in the working area of Block A, Kapuas Regency. Obtained 9 variables with 43 indicators of factors that cause waste which are the basis for this research. The method used is the severity index method to obtain the dominant and main factors causing waste. The results of this study are the dominant and main factors for the occurrence of waste, namely with codes A1, A6, B2, B3, B6, D4, E4, E6, F6, I12 with a moderate risk category, based on the severity index value, the dominant causative factor risk response is transfer.